Demonstrating deservingness and dignity. Symbolic boundary work among Syrian refugees - Vandevoordt, R; Verschraegen, G (Elsevier, 2019)
While the literature on boundary making has mainly documented variations in boundary work between groups and institutional contexts, scholars have paid less attention to boundary work in the context of unexpected dislocation of a group to a new context. This article examines how Syrian refugees in Belgium deal with a sudden loss of social status, by analysing how they draw symbolic boundaries among themselves, established immigrants and native Belgians. Drawing on 26 in-depth interviews with 39 Syrian refugees as well as on-going participant observation, we describe how our respondents use ‘comparative strategies of self’ to position themselves as dignified and worthy individuals. We present two types of moral, and two types of cultural boundary work our interlocutors engaged in. They stressed their moral worthiness by, first, distancing themselves from the bad behaviour of ‘uneducated’ refugees in reception centres, and from established immigrants in materially deprived urban neighbourhoods. Second, especially male interlocutors displayed a strong work ethic highlighting how they renegotiated their masculine worthiness in response to their loss of status and their refugee condition. In addition, they demonstrated their cultural qualities by articulating, first, their personal competences and aesthetic refinement as individuals, and, second, by highlighting the general level of education, wealth and cultural achievements of Syrian people as a whole. In sum, these four boundary-making strategies served to legitimise their presence and strengthen their position vis-à-vis other social groups such as their compatriots, established immigrants and native Belgians. In line with previous studies by Sherman (2005) and Purser (2009), we find that these moral and cultural boundaries are significant in reasserting disadvantaged individuals’ sense of dignity, whilst working against the emergence of solidarity between wider groups of immigrants in similar socio-structural positions.